2009
DOI: 10.1007/s12170-009-0032-9
|View full text |Cite
|
Sign up to set email alerts
|

Women and smoking cessation: Challenges and opportunities

Abstract: Tobacco smoking remains the most common preventable cause of death and disability in the United States. Although greatly decreased since the 1960s, the prevalence of smoking among women continues to be problematic because of the absolute prevalence and the continued increase in illnesses that take a long time to manifest (eg, lung cancer) in former smokers. Although no consensus exists, a number of research studies, meta-analyses, and reviews have concluded that quitting smoking appears to be more diffi cult f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…[19][20][21][22][23] Thus, alternative smoking cessation programs are needed to assist women who cannot quit with self-help or with pharmacologic approaches. 24 Exercise was initially proposed as a therapy for smoking cessation among women because it may help offset weight gain and concerns regarding weight gain, both of which are important barriers to cessation among women. [25][26][27][28][29][30] Previous studies by our research group and others have not consistently shown an exercise-mediated effect on weight gain or weight concerns but have instead more generally demonstrated that traditional aerobic exercise programs (i.e., brisk walking, bicycling) incorporated into smoking cessation treatment result in higher quit rates compared with smoking treatments without exercise.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Thus, alternative smoking cessation programs are needed to assist women who cannot quit with self-help or with pharmacologic approaches. 24 Exercise was initially proposed as a therapy for smoking cessation among women because it may help offset weight gain and concerns regarding weight gain, both of which are important barriers to cessation among women. [25][26][27][28][29][30] Previous studies by our research group and others have not consistently shown an exercise-mediated effect on weight gain or weight concerns but have instead more generally demonstrated that traditional aerobic exercise programs (i.e., brisk walking, bicycling) incorporated into smoking cessation treatment result in higher quit rates compared with smoking treatments without exercise.…”
Section: Introductionmentioning
confidence: 99%